Low-skilled Immigration and Parenting Investments of College-educated Mothers in the United States: Evidence from Time-use Data - Catalina Amuedo-Dorantes; Almudena Sevilla-Sanz (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
This paper uses several decades of US time-diary surveys to assess the impact of low-skilled immigration, through lower prices for commercial child care, on parental time investments. Using an instrumental variables approach that accounts for the endogenous location of immigrants, we find that low-skilled immigration to the United States has contributed to substantial reductions in the time allocated to basic child care by college-educated mothers of non-school age children. However, these mothers have not reduced the time allocated to more stimulating educational and recreational activities with their children. Understanding the factors driving parental time investments on children is crucial from a child development perspective.
Keywords: J61; J22; J13; 330; Parental Time Investment; Immigration; Education Gradient; Time Use